PENGEMBANGAN MEDIA KOMIK MUATAN IPAS MATERI EKOSISTEM UNTUK SISWA KELAS V SDN 27 CAKRANEGARA - Kelandia, Isfawani; Liwa Ilhamdi, Mohammad; Wira Zain Amrullah, Lalu; Syazali, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop comic media for the Natural and Social Sciences (IPAS) subject for material on ecosystems for grade V students at SDN 27 Cakranegara. The research method used is Research and Development (R&D) with the Hannafin and Peck model approach which includes needs analysis, design, and development and implementation. This study involved all grade V students at SDN 27 Cakranegara, consisting of 35 students and 1 teacher. The results of this study are IPAS comic media containing material on the interaction of biotic and abiotic ecosystems. Based on validation by media experts, this comic obtained an average feasibility percentage of 90.7% and from validation by material experts obtained a percentage of 90%. In addition, the results of small and large scale trials, involving teacher and student responses, indicate that this comic media is included in the very feasible category.